Design of Wayang Show With 360° Video (Virtual Reality) as a Media to Intoduce Teenage About Wayang Cepak Tegal - Lutfi Firmansyah; Taufan Hidayatullah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Nowadays, wayang cepak in Tegal City are increasingly rarely known by young people, especially teenagers wayang performances being rarely attended. From this study, it is known that adolescents tend to be more interested in westernized modern culture so that they are indicated to have less respect and are increasingly unfamiliar with their own existing traditional culture. The purpose of this research is to reintroduce the wayang cepak in the form of digital media which is shown to teenagers in Tegal City aged 15-21 years. The delivery of story content through Virtual Reality has the potential to provide an immersive viewing experience that can be viewed from a 360° video perspective using the Luther-Sutopo version of the Multimedia Software Development Method for the segmentation of teenagers aged 15-21 years. To find out and collect data the researchers used qualitative methods. The results of this study are expected to help re-introduce and invite teenagers to generate a sense of love for wayang cepak. As well as looking for alternative ways to watch wayang shows from a 360° perspective as a whole for Virtual Reality users. Virtual Reality is an effective promotional media that utilizes new technology to add to the audience's new experience of an environment as a whole, so that here it is hoped that the audience will enjoy the Wayang Cepak performances that contain the values of good moral teachings through various stories.